2012
DOI: 10.1007/s10554-012-0009-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Brugada syndrome by cardiac magnetic resonance

Abstract: Brugada syndrome (BrS) has been originally considered to occur in structural normal hearts. However recent pathological and imaging data suggest that structural and functional changes may be present in this syndrome. This study was designed to elucidate whether any macroscopic heart abnormality is detectable in patients with BrS. For this purpose we used cardiac magnetic resonance (CMR). Twenty-nine patients displaying the BrS type-1 ECG pattern and 29 healthy controls underwent CMR (1.5 Tesla). Left (LV) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 22 publications
1
17
1
Order By: Relevance
“…Studies have demonstrated significantly larger RVOT area and reduced RVOT ejection fraction in BrS patients compared with normal controls[ 5 , 6 , 13 , 14 ]. However this has not been a universal finding[ 26 ]. Using quantitative analysis of the RV and RVOT, we confirmed that the overall incidence of RVOT morphologic abnormalities was high, being 67% in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated significantly larger RVOT area and reduced RVOT ejection fraction in BrS patients compared with normal controls[ 5 , 6 , 13 , 14 ]. However this has not been a universal finding[ 26 ]. Using quantitative analysis of the RV and RVOT, we confirmed that the overall incidence of RVOT morphologic abnormalities was high, being 67% in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…While some studies have demonstrated either decreased RV systolic function or increased RV dimensions, others have found no increased prevalence of abnormal findings as compared to a control population. 13,14 Evidence of LGE was noted in 1 of 2 studies with 8% in BS patients vs 0% in matched controls (P 5 .028). 13,14 Furthermore, 1 study of T1 mapping showed 20% prevalence of elevated T1 signal consistent with fat signal, a marker of AC, in BS patients vs none in controls.…”
Section: Discussionmentioning
confidence: 96%
“…Similarly, in a study of 30 BrS patients compared to 30 age and sex matched controls, the BrS patients were found to have higher incidence of mild RV wall motion abnormalities, reduced RVOT EF and increased RV inflow tract diameter with no fatty infiltration seen in either group . However, these morphologic changes may be heterogeneous because the finding of structural abnormalities was not replicated in another cMRI study of 29 BrS patients compared with 20 normal controls …”
Section: Heterogeneity In Cardiac Morphologymentioning
confidence: 97%